Cover Image. Issue 6 (18th March 2020) - Lai, Han; Wang, Song; Zhao, Yajun; Qiu, Chen; Gong, Qiyong
Abstract : COVER ILLUSTRATION The morphological variations in bilateral putamen (illustrated as red brain areas) was associated with interindividual differences in dispositional optimism in late adolescence. Importantly, this association was found to be explained by extraversion, which has the characteristics of positive affection (illustrated as rainbow), revealing the importance of extraversion as an essential personality factor for dispositional optimism acquisition.